Walking and talking: The effect of smartphone use and group conversation on pedestrian speed - Walsh, Lexie Reynolds; Xian, Tingsen (Tim); Levinson, David Matthew; Rayaprolu, Hema Sharanya (TeMA - Journal of Land Use, Mobility and Environment, 2019)
Distracted walking due to smartphone use is on the rise resulting in growing concern over pedestrian safety and well-being. Our study measured the walking speeds of pedestrian groups differentiated by their smartphone use in two different environments - a wide pedestrian bridge at a university, and a narrow footpath on a busy commercial street. The results show that groups of people, phone users, and often followers of phone users, walk significantly slower than solo walkers uninfluenced by phone. Especially on the narrow street, people in groups and phone users are seen to not only slow themselves down but also slow the people walking behind them.